Anti-Theft Flooring System using ESP32 - K, Ajmal; Muthiyil, Arun Suresh; M, Junaidh Haneefa; Nihal M; S, Reshmi C (Journal of Electronics and Informatics, 2024)
The ESP32-powered anti-theft flooring system represents an innovative and cost-effective solution designed to enhance security across various settings, including homes, businesses, and diverse locations. At its core, the system comprises a network of strategically placed pressure sensors concealed beneath a flooring mat, seamlessly integrated with the ESP32 microcontroller featuring built-in Wi-Fi and a camera. When an object exceeding a predetermined weight threshold traverses the mat, the embedded sensors swiftly activate the ESP32, prompting it to capture a photograph of the event. This image is then promptly forwarded to a pre-configured email address, offering real-time visual insights into potential security breaches. Furthermore, the ESP32 can be programmatically configured to activate an audible alarm, providing an additional layer of security and acting as a powerful deterrent. The system’s design emphasizes user-friendliness, ease of installation, and adaptability to various environmental needs. Its customization options enable users to tailor the system to specific requirements, ensuring a seamless integration into any given space. Importantly, safety measures have been incorporated to prevent false alarms triggered by smaller entities, as the pressure sensors only respond to objects surpassing a predefined weight. Beyond its primary function of theft prevention, the ESP32 anti-theft flooring system unveils a realm of creative possibilities. Its applications extend to smart home automation, traffic monitoring, and even livestock tracking, showcasing the system’s versatility and adaptability in addressing diverse challenges. This multifaceted approach positions the ESP32 system not only as a robust security solution but also as a catalyst for innovation in various technological domains.
Keywords: ESP32 Microprocessor; AI; Anti-Theft Flooring System; Home Automation.